Multifaceted therapeutic options for stress urinary incontinence in women - Aleksandra Osińska; Cezary Stawikowski; Bartłomiej Zielonka; Barbara Dengler; Izabela Wolanin; Paulina Krawiec; Ilona Kowalczyk; Bartłomiej Stachyra; Marta Wolanin; Karolina Madej (Kazimierz Wielki University, 2023)
Stress urinary incontinence (SUI) affects many women worldwide in every age group. Involuntary leakage of urine during abdominal pressure increase significantly reduces the quality of life. The choice of treatment depends on the patient's expectations, the doctor's experience and the severity of symptoms. Aim of the study: The aim of this study is to discuss the therapeutic methods of stress urinary incontinence (SUI). Material and method: The work was based on a review of the available literature in the PubMed, Google and Google Scholar databases using the following keywords: stress urinary incontinence; SUI; urinary incontinence in women; Surgical treatment; TOT; TVT. Results and conclusions: We use conservative and surgical methods in the treatment of stress urinary incontinence. Conservative treatments such as physiotherapy, pharmacotherapy, and behavioral therapy are first-line treatments. In the case of severe symptoms of stress urinary incontinence, surgical treatment is used. The most common method is the Burch operation and TVT and TOT sling operations. Treatment of stress urinary incontinence (SUI) in women requires an approach that takes into account the patient's goals, severity of symptoms, desired effect, physician experience and complications, therefore there is no single effective management.